ANALISIS KETENAGAKERJAAN DAN PARTISIPASI ANGKATAN KERJA SEBELUM DAN PADA MASA PANDEMI COVID-19 DI LAMPUNG - Febiyana Qomariyah (P3M STISIPOL Dharma Wacana Metro, 2022)
1 Statistisi Ahli Madya pada Badan Pusat Statistik (BPS) Provinsi Lampung Jl. Basuki Rahmat No. 54 Teluk Betung, Bandar Lampung, Lampung, Indonesia *Korespondensi: febiyana.q@gmail.com Recieved: 20/09/2021|Revised: 10/06/2022|Accepted: 15/06/2022 Abstract The Covid-19 pandemic has had a tremendous impact on working conditions in Indonesia, and Lampung is no exception. This study aims to study Lampung's employment structure in detail from the Manpower, Labor Force and Labor Force Participation Rate based on age and education level completed before and during the Covid-19 pandemic. This study uses data from the processing of the Lampung Province National Labor Force Survey (Sakernas) contained in the publication of the State of the Lampung Province Workforce in 2019 - 2020. The data used in this study is data on the Manpower, Labor Force and Labor Force Participation Rate (TPAK), which is differentiated by urban and rural areas. In addition, the data used are also differentiated according to age and level of education completed. The use of descriptive statistical analysis was carried out to describe labor conditions in Lampung before the Covid-19 pandemic and during the Covid-19 pandemic. The study and analysis of employment and TPAK before and during the Covid-19 pandemic in Lampung showed that the composition of the workforce, labor force and TPAK in rural areas was greater than in urban areas. This occurs in all age groups and education levels.